ANALYSIS OF TIME AND COST PERFORMANCE IN THE COMPLETION OF THE CONSTRUCTION PROJECT FOR THE REGIONAL DISASTER MANAGEMENT AGENCY (BPBD) BUILDING COMPLEX IN PASURUAN REGENCY, BUDGET YEAR 2023 - Bagus Cahyono; Risma Marleno; Wateno Oetomo (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
In the construction project of the Pasuruan Regency BPBD building complex, which is currently still ongoing, has experienced problems related to the schedule for the implementation of its activities. The problem in question is the delay in the schedule for the implementation of its activities, where the results of the progress realization are not in accordance with the schedule plan, through this writing an evaluation is carried out related to performance in the field through an approach using. The data analysis process is carried out by calculating analysis indicators including BCWS, BCWP and ACWP, the calculation of cost indicators consists of calculating the CV value, Cost Performance Index (CPI), ETC and EAC, and also calculating related to time indicators including calculating the SV value, Time Performance Index (SPI) and also calculating the time requirements / Estimated time (TE) in project completion. Based the results of  calculation / data analysis that has been carried out, the Cost Performance Index value CPI> 1 is obtained, and the SPI Time Performance Index value < 1, indicating that the realization cost is still below the plan cost with the achievement of progress realization which is also still below the plan schedule. while for the ETC value of project completion of Rp.2,148,176,877,000..148,176,877.17 with an EAC value of Rp.16,624,276,448.77 from the total contract value of Rp. 18,898,770,576.77. and related to the estimated time requirement for project completion (TE) obtained a time of 220.75 ⁓ 221 days, 11 days later than the time provided 210 days.